Long‐term prognosis of patients with Ehlers‐Danlos syndrome and epilepsy. Issue 8 (25th June 2014) - Verrotti, Alberto; Spartà, Maria Valentina; Monacelli, Debora; Porto, Rossella; Castagnino, Miriam; Russo Raucci, Annalisa; Compagno, Francesca; Viglio, Simona; Foiadelli, Thomas; Nicita, Francesco; Grosso, Salvatore; Spalice, Alberto; et al.
Summary Objective Epilepsy in Ehlers‐Danlos syndrome (EDS) has been reported in the literature, but there are no studies that have investigated in detail clinical and electroencephalography (EEG) features in patients with EDS, and that have compared the outcome of epilepsy in subjects with or without brain lesions. We report a series of 42 patients with EDS and epilepsy, including data that concern clinical characteristics, EEG abnormalities, brain malformations at magnetic resonance imaging (MRI) and long‐term outcome. Methods EEG, clinical information, and neuroimaging characteristics in 42 patients with EDS were analyzed at the onset of epilepsy and after long‐term follow‐up (at least 5 years). We subdivided the patients into two groups: group A, 26 patients without brain abnormalities; group B, 16 patients with brain lesions, often with periventricular heterotopia (PH). Results Group A patients: Most cases (19 of 26) presented focal epilepsy, whereas 7 of 26 were affected by generalized epilepsy; interictal EEG showed temporal or temporoparietal spikes in most cases. Twenty‐three patients received antiepileptic drug (AED) monotherapy; three patients were treated with polytherapy. During follow‐up, all patients were seizure‐free for at least 2 years, and only one continued to receive AEDs. Group B patients: the majority presented focal epilepsy (9 of 16), but many patients had generalized epilepsy (7 of 16); interictal EEG showed usually frontal or frontotemporal spikes and waves. Many patients (12 of 16) received AED polytherapy. During follow‐up, 12 patients were seizure‐free, and all patients continued pharmacologic treatment. Significance All patients without brain lesions showed a favorable response to AED monotherapy and were seizure‐free after a few years of treatment. Patients with central nervous system abnormalities had a worse outcome, suggesting that the presence of brain lesions could influence the long‐term evolution in these patients. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.